2005
DOI: 10.1529/biophysj.104.056515
|View full text |Cite
|
Sign up to set email alerts
|

The Physics of Filopodial Protrusion

Abstract: Filopodium, a spike-like actin protrusion at the leading edge of migrating cells, functions as a sensor of the local environment and has a mechanical role in protrusion. We use modeling to examine mechanics and spatial-temporal dynamics of filopodia. We find that >10 actin filaments have to be bundled to overcome the membrane resistance and that the filopodial length is limited by buckling for 10-30 filaments and by G-actin diffusion for >30 filaments. There is an optimal number of bundled filaments, approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
443
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(484 citation statements)
references
References 53 publications
40
443
1
Order By: Relevance
“…The probing mechanism is strongly connected to filopodia length. Literature data report an average length of filopodia of the order of 1-5 mm [15,25,26]. We confirmed that this dimension is still valid in the case of micropatterned surfaces.…”
Section: Discussionsupporting
confidence: 82%
“…The probing mechanism is strongly connected to filopodia length. Literature data report an average length of filopodia of the order of 1-5 mm [15,25,26]. We confirmed that this dimension is still valid in the case of micropatterned surfaces.…”
Section: Discussionsupporting
confidence: 82%
“…Filopodium is a spike-like protrusion that contains compact F-actin bundle structure; it functions as a sensor of the local environment and has a mechanical role in cell protrusion [31]. For example, the F-actin bundle protein Fascin could elicit spike-like filopodia formation, which is important for cell migration [32].…”
Section: Over-expression Of 2ig Increases Spike-like Filopodia Formationmentioning
confidence: 99%
“…Individual actin filaments are flexible and insufficient for membrane protrusion. Bundling of actin filaments provides rigidity against the compressive force from the plasma membrane 12 .…”
mentioning
confidence: 99%